Ecofriendly and enhanced biogenic synthesis of silver nanoparticles using deep eutectic solvent-based green tea extracts. (15th December 2022) - Liu, Yuli; Kang, Seulgi; Li, Ke; Chen, Jingyan; Bae, Boyeon; Hwang, Inseon; Ahn, Eun-Young; Park, Youmie; Chun, Kwang-Hoon; Lee, Jeongmi
Abstract: In compliance with green chemistry, metallic nanoparticles can be biogenically synthesized using plant extracts. Herein, three different deep eutectic solvents (DESs) were used instead of water to prepare green tea extracts (GTEs). The resultant DES-based GTEs exerted different beneficial effects on the biosynthesis of silver nanoparticles. Compared with the water-based GTE (W-GTE), the DES-based GTEs contained higher levels of catechins (up to 235% more) that are natural reducing and capping agents and showed higher synthesis efficiency. In particular, two DESs, which consist of glycerol and betaine with a common urea molecule and are designated as GU and BU, respectively, could produce silver nanoparticles with superior properties to water. Specifically, GU- and BU-GTE-based silver nanoparticles showed uniformly reduced sizes, 39.12 (±5.33) nm and 43.11 (±6.42) nm, respectively and homogenous face-centered cubic crystallinity. DESs added to W-GTEs lead to synthesis of silver nanoparticles with improved dispersion. The DES-GTE-based silver nanoparticles at 60 μg/mL displayed in vitro anti-cancer activity comparable to doxorubicin at 12.5 μg/mL. These results suggest that the tested DESs could serve as efficient extraction solvents for phytochemicals as well as effective surface modifiers without posing adverse effects for subsequent applications of the synthesized nanoparticles. The favorable effects of GU and BU were found to partially involve ammonia, which was formed during DES preparation at high temperatures (≥80 °C). This study shows that DESs can promote the biogenic synthesis of silver nanoparticles by playing diverse roles depending on the unique properties of the DESs and their constituents. Highlights: DES-based green tea extracts were used to synthesize AgNPs for the first time. DESs exert constructive effects on synthesis efficiency, particle size, and dispersion. DESs can efficiently extract phytochemicals (reducing and end capping agents). DESs can also serve as effective surface modifiers of AgNPs. Ammonia unintentionally produced in DESs can affect the AgNP biosynthesis.